过盈联接对空心轴内花键的影响及分析 - 张志宏; 张和平; 刘忠明; 张立勇; 孟令先; 李纪强; 王征兵; 王振 (Jixie chuandong)
For the structure that its outer surface is used in an interference fit and its inner bore is for a spline joint,the interference amount,the fit diameter and the heating temperature are designed,the effects of the fit diameter on the interference amount and inner bore size are studied in detail,the deformation amount of internal and external spline owing to the interference and torsion deflection are respectively calculated,and the modification curve of the longitudinal tooth shape for the external spline is finally proposed.